A study of Heart Rate Variability (HRV) in healthy offsprings with parental history of type 2 diabetes mellitus - Pokhrel, Suman; Agrawal, Kopila; Dev, Santosh; Shakya, Binnam; Gajuryal, Sharad Hari (Birat Journal of Health Sciences, 2022)
Introduction: Type 2 diabetes mellitus (T2DM) is a heterogeneous polygenic metabolic disease condition that is caused by insulin resistance leading to hyperglycemia. Since, T2DM is genetically inherited and autonomic dysfunction is its major complications, healthy offsprings of diabetic parents are highly vulnerable to manifest dysautonomia leading to insulin resistance. Objectives: We aimed to assess cardiac autonomic function using heart rate variability (HRV) parameters in healthy offsprings having parental history of T2DM. Methodology: A comparative cross-sectional study was carried out in the laboratory of department of Physiology enrolling 30 healthy offsprings of non-diabetic parents (Group 1) and 30 healthy offsprings of diabetic parents (Group 2). Anthropometric, biochemical and cardiovascular variables were assessed using standard procedures. Time domain and frequency domain parameters of HRV spectrum were assessed using photoplethysmography principle. Results: HRV findings revealed that markers of sympathetic regulation were significantly higher and those of parasympathetic function were significantly reduced in subject group having parental history of T2DM. LF/HF ratio was significantly increased suggesting sympatho-vagal imbalance in offspring of diabetic parents even in their euglycemic state. Conclusion: Alteration of cardiovascular autonomic function is found in healthy offspring of diabetic parents, characterized by reduced vagal activity and pronounced sympathetic regulation. Assessment of cardiac autonomic function would help in timely detection of such dysautonomia and reducing the life-threatening effects on offspring having parental history of T2DM.